PRRSV-1 induced lung lesion is associated with an imbalance between costimulatory and coinhibitory immune checkpoints - Ruedas-Torres, Inés; Sánchez-Carvajal, José María; Carrasco, Librado; Pallarés, Francisco José; Larenas-Muñoz, Fernanda; Rodríguez-Gómez, Irene Magdalena; Gómez-Laguna, Jaime (Frontiers in Microbiology, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) induces a dysregulation on the innate and adaptive immune responses. T-cell activation requires a proper interaction and precise balance between costimulatory and coinhibitory molecules, commonly known as immune checkpoints. This study aims to evaluate the expression of immune checkpoints in lung and tracheobronchial lymph node from piglets infected with two PRRSV-1 strains of different virulence during the early stage of infection. Seventy 4-week-old piglets were grouped into three experimental groups: (i) control, (ii) 3249-infected group (low virulent strain), and (iii) Lena-infected group (virulent strain) and were euthanized at 1, 3, 6, 8, and 13 days post-infection (dpi). Lung and tracheobronchial lymph node were collected to evaluate histopathological findings, PRRSV viral load and mRNA expression of costimulatory (CD28, CD226, TNFRSF9, SELL, ICOS, and CD40) and coinhibitory (CTLA4, TIGIT, PD1/PDL1, TIM3, LAG3, and IDO1) molecules through RT-qPCR. Our findings highlight a mild increase of costimulatory molecules together with an earlier and stronger up-regulation of coinhibitory molecules in both organs from PRRSV-1-infected animals, especially in the lung from virulent Lena-infected animals. The simultaneous expression of coinhibitory immune checkpoints could work in synergy to control and limit the inflammation-induced tissue damage. Further studies should be addressed to determine the role of these molecules in later stages of PRRSV infection.